Karyotype analysis of some Tragopogon L. taxa from Turkey - Kiran, Yasar (Univ Tokyo Cytologia, 2024)
This study investigated the somatic chromosome numbers and morphometric properties of chromosomes in eight taxa belonging to the genus Tragopogon L. (Asteraceae) from Turkey. These taxa are T. buphthalmoides var. buphthalmoides (DC.) Boiss., T. buphthalmoides var. latifolius Boiss., T. coloratus C.A.Mey., T. dubius Scop., T. latifolius Boiss., T. porrifolius L., T. porrifolius subsp. longirostris (Sch. Bip.) Greuter, and T. reticulatus Boiss. & Huet. Chromosome numbers in most of the studied taxa were determined 2n=2x= 12, while T. reticulatus 2n=4x= 24, was determined. The genus Tragopogon is characterized by a basic chromosome number x = 6. Satellites were observed in all studied taxa. Using the Stebbins classification system, taxa were categorized as class 2B or 3B. Additionally, various parameters such as chromosome length, haploid chromosome length, relative length, arm ratio, centromere states, karyotype asymmetry values, and karyotype formula were determined. The karyotype formulas of 7 of the 8 taxa included in the study (except T. dubius) were revealed by us for the first time.
Keywords: Asteraceae; Tragopogon; Chromosome number; Karyotype Analysis; Turkey